Screen Time and Attention Subdomains in Children Aged 6 to 10 Years - Magnus Liebherr; Mark Kohler; Julia Brailovskaia; Matthias Brand; Stephanie Antons (MDPI AG, 2022)
Using digital media has become the most popular leisure activity for children and adolescents. The effects of digital media use on the developing brain and cognitive processes of children are subject to debate. Here, we examine the effect of digital media use on attention subdomains in children aged 6 to 10 years. In total, 77 children participated in the study. Selective and divided attention as well as switching between attentional subdomains were quantified by the SwAD-task. Parents were asked to assess the screen time of their children (smartphone, laptop/PC, game console, tablet, TV). Results show no main or interaction effects of screen time on any of the attention conditions investigated. Based on the present findings as well as previous studies, we suggest a possible non-linear relationship between the amount of screen time and attention function. Furthermore, we emphasize the relevance of considering the socio-economic background of children and a need for longitudinal studies.